Ranibizumab for the treatment of retinopathy of prematurity: systematic review and meta-analysis - Alva, Niza; Martínez, Alex R.; Ortiz-Saavedra, Brando; Montes-Madariaga, Elizbet S.; Cotrina, Alonso; Caballero-Alvarado, José A.; Sah, Ranjit; Barboza, Joshuan J. (Frontiers in Pediatrics, 2023)
Anti-VEGF drugs like ranibizumab can be used to treat retinopathy of prematurity (ROP) by halting the formation of abnormal blood vessels, or lasers can be used to burn the edges of the retina where these vessels are present. The objective is to compare the efficacy for ROP between ranibizumab and laser therapy. Material and methods Electronic searches will be carried out in medical databases with key words and controlled vocabulary terms. Randomized controlled trials (RCT) will be assessed. The primary outcome will be the full ROP regression. Two reviewers will extract the data using predefined forms and, to assess the quality of the study, we will use RoB 2.0, the tool for randomized controlled trials developed by the Cochrane Collaboration. We used a combination of the inverse-variance approach and random-effects models for the meta-analysis. Results The eyes of 182 preterm infants who had ranibizumab treatment were assessed in a total of 364 eyes, and 135 infants received laser therapy. The follow-up period was between 6 and 24 months. Ranibizumab was not associated with greater regression of ROP compared to laser therapy in preterm infants (RR: 1.09, CI 95%: 0.95–1.24; p: 0.22). Also, ranibizumab was not associated with recurrence of ROP compared to laser therapy in preterm infants (RR: 3.77, CI 95%: 0.55–25.81; p: 0.22). Conclusions The efficacy of ranibizumab compared to laser is very uncertain in terms of ROP regression and decreased ROP recurrence in preterm infants. Systematic Review Registration identifier PROSPERO (CRD42022324150).